Capacitance–voltage spectroscopy and analysis of dielectric intrinsic amorphous silicon thin films. Issue 10 (11th July 2016) - Gerke, Sebastian; Micard, Gabriel; Job, Reinhart; Hahn, Giso; Terheiden, Barbara
Abstract: Capacitance‐voltage (CV) spectroscopy of classic metal‐insulator‐semiconductors (MIS) using insulating oxides as well as highly passivating intrinsic and hydrogenated amorphous silicon ((i) a‐Si:H) has been discussed extensively in literature, particularly with regard to photovoltaic applications. Imperfectly passivating as well as thermal or light‐induced degraded (i) a‐Si:H exhibits a reduced passivation quality and an increased defect‐based shunt conductivity. These properties cannot be accounted for by classical CV spectroscopy as described in literature for insulating oxides or highly passivating (i) a‐Si:H. To characterize such imperfectly passivating or degraded (i) a‐Si:H thin films by CV spectroscopy, the required MIS samples have to be prepared following special design rules. Design rules were defined on the base of electric field FEM investigations and empirically validated. In combination with an adapted approach to calculate the number of defects ( ND ) CV spectrometry becomes a more reliable analytic tool to describe imperfectly passivating as well as degraded (i) a‐Si:H. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)